Proses Penyelesaian Perselisihan Kepentingan di PT Holcim Indonesia Tbk (Studi Kasus di Pengadilan Hubungan Industrial pada Pengadilan Negeri Semarang) - Jaya, Arief Rakhmatan; , Nuswardhani, S.H, S.U; , Darsono, S.H, M.H (2015)
This study aims to determine the consideration, determine the decision on the evidence and the legal consequences of the verdict in the case of conflict of interest in PT Holcim Indonesia Tbk. The research method using descriptive normative. The type and source of data consisted of secondary data, primary legal materials, secondary and tertiary, while the primary data includes interviews with relevant parties. The method of data collection by the collection of secondary data is literature study with the primary data and interviews. While data analysis techniques with qualitative analysis. The results showed that the judge in determining the consideration of evidence in the case of conflict of interest in PT Holcim Indonesia Tbk, in the Industrial Relations Court, with No. 24/Rev-Sus-PHI/G/2014/PN.SMG considers two things: the consideration of the sitting his case or about the events and legal considerations. The judge considered that the evidence made by the Plaintiff is not proven, while the evidence by the respondent proved because there is compatibility between the written evidence and the evidence of witnesses. The judge also considered the lawsuit of the Plaintiff that do not qualify formal lawsuit. That's because the discrepancy between the contents posita and petition, thus making the suit blur (Obscuurlibel). This is in accordance with its legal basis, namely Article 8, paragraph 3 RV stating that: "Base lawsuit that contains a description of events or occurrences include the reasons based on the circumstances and the description of the legal grounds (posita / fundamentum petendi)". On these considerations, the then Justice in its decision ruled that the lawsuit the plaintiff can not be accepted NO (Niaet Ontvankelijke verklaard), whereas the legal effect of the decision of the judge in the case of conflict of interest in PT Holcim Indonesia Tbk, for Plaintiff the decision resulted in the plaintiff can not be receive a bonus as they want, and for the Defendant has no obligation to pay a bonus, especially in the year 2013 due to the burden of EBITDA established by the company was not able to be met by employees.